Influence of microstructure on fatigue property of ultra high-strength steels - Kanji OKUDA; Kazuhiro OGAWA; Yuji ICHIKAWA; Tsuyoshi SHIOZAKI; Naoki YAMAGUCHI (Fracture and Structural Integrity)
Ultra-high-strength steels (with tensile strength higher than 980 MPa) are widely used in automobile manufacturing owing to their lightweight that contributes to fuel efficiency. The fatigue strength of ultra-high-strength steels with a notch tends to decrease, which is known as the effect of notch sensitivity. In this study, 4-point bending fatigue tests were performed to examine the fatigue strength and notch sensitivity of four steels; namely 590 MPa class steel, 980 MPa class martensitic steel, 980 MPa class bainitic steel, and 980 MPa class precipitation hardening steel plates with three different stress concentration factors. The results indicate that the fatigue strength and notch sensitivity of 980 MPa class steel specimens were higher than those of 590 MPa class steel specimens. The notch sensitivities of tested plate specimens were lower than those reported for cylindrical specimens of bainitic ultra-high-strength steels. Fatigue crack observation revealed that the cracks initiated in 590 MPa class steel, 980 MPa class bainitic, and martensitic steel propagated southward from the lowest bottom of notch. Although similar initial crack propagation pattern was detected in precipitation hardening steel, the crack changed direction when it reached the central part of the specimen.